ANALYSIS OF ESTROGEN RECEPTOR (ER) AND PROGESTRONE RECEPTOR (PR) EXPRESSION IN SURFACE EPITHELIAL TUMORS OF OVARY AND ITS CORRELATION WITH THEIR CLINICAL STAGE - Madeeha Anwar (Army Medical College Rawalpindi, 2018)
Objective: To evaluate ER and PR expression in epithelial ovarian cancers (EOC) and to determine its association with clinical stage. Study Design: Cross sectional study. Place and Duration of Study: Histopathology department, Armed Forces Institute of Pathology (AFIP) Rawalpindi, from Mar to Oct 2017. Material and Methods: A total of thirty three (n=33) histologically confirmed EOCs were analyzed. ER and PR expression status was assessed by immunohistochemistry using Allred scoring system and was compared with the clinical stage defined by The International Federation of Gynecology and Obstetrics (FIGO) staging system. Results: A total of thirty three (n=33) females were enrolled. Mean age of the study females was 50.8 ± 12.9 years. Most frequent histologic type was serous carcinoma (SC) 60.6% (n=20) followed by mucinous carcinoma (MC) 15.2% (n=5), endometrioid carcinoma (EC) 9.1% (n=3), clear cell carcinoma (CC) 9.1% (n=3), Brenner tumor (MBT) 3% (n=1) and seromucinous carcinoma (SMC) 3% (n=1). Most patients were in clinical stage I 61% (n=20) followed by stage II 24%, (n=8) and stage III 15% (n=5). Among SC, 90.0% (n=18/20) were ER and 65% (n=13/20) were PR-positive. All MC and CC were ER/PR negative. Two of the three ECs were ER and one was PR-positive. Higher percentage of stage I tumors exhibited ER 65% (n=13/20) and PR 45% (n=9/20) positive status (p>0.5). The correlation was very weak positive between clinical stages and both ER and PR scores (Allred) r=0.11 and 0.15 respectively p>0.05. Conclusion: Higher percentages of stage I tumors exhibited ER and PR positive status yet not statistically significant from stage II/III. Estimation of ER and PR receptor status may help to select the women with ovarian malignancy for hormonal therapy, which is more likely to improve the response rate.